PENGAMBILAN KEPUTUSAN INVESTASI CRYPTOCURRENCY PADA INVESTOR MUDA - Simanjuntak, Agus Nakkok; Aruan, Hicca Maria Gandi Putri; Sidabutar, Rimbun C. D.; Naulibasa, Maria Oktavia (JURNAL LENTERA BISNIS, 2025)
This study focuses on how bitcoin investment decisions can be influenced by financial literature and fear of missing out (FoMO). In this study, high school students in Medan and members of the Zoomers Generation (Gen Z) at HKBP Nommensen University completed a Likert-scale survey. Additionally, Partial Least Squares (PLS) analysis of the gathered data was performed using SmartPLS 4 software. The test findings show that both can greatly enhance investment choices in cryptocurrencies.